Sierra Leone : 2019 Article IV Consultation, Second Review Under the Extended Credit Facility Credit Facility Arrangement, Request for a Waiver of Nonobservance of Performance Criterion, and Financing Assurances Review. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses Sierra Leone's 2019 Article IV Consultation, Second Review Under the Extended Credit Facility Arrangement, Request for a Waiver of Nonobservance of Performance Criterion. Sierra Leone continued to make good progress under the IMF-supported program. While the program's medium-term goals remain appropriate to enable future growth and development, the dramatic onset of the global coronavirus disease 2019 pandemic poses significant near-term risks. Combating the economic fallout of the crisis and protecting the health of Sierra Leoneans should be the immediate priority. The authorities' cautious fiscal policy has been important. They have made commendable progress in mobilizing domestic revenue and prudent execution of budgeted expenditures. This has stabilized domestic borrowing needs and allowed inflation pressures to ease. Managing fiscal risks and securing debt sustainability remain the medium-term priority. Continued revenue mobilization will require both tax administration and policy reforms. Deeper public financial management reforms will further improve budget planning and execution, including preventing new arrears. A strategic plan for the two state-owned banks will be instrumental in addressing underlying fiscal risks.